Learning obstacles in the generalization process: In case number pattern topic - Nyla Farhatul Maula; Didi Suryadi; Al Jupri (Research and Development in Education (RaDEn), 2024)
Generalization plays an important role in mathematics because it is considered inherent in mathematical thinking in general. Where number pattern is a topic that is closely related to generalization. Problems are still found in generalizing number patterns so this can cause learning obstacles. This research aims to identify learning obstacles for Junior high school students in the generalization process with a focus on number pattern topics. This research is qualitative research with a case study method. The research subjects consisted of 30 grade 8 students in Jakarta who had studied number pattern. Subjects were given three test tasks, the results of which were used to figure out learning obstacles in the generalization process experienced by students and then continued with interviews with ten subjects. The findings show that learning obstacles in the pattern generalization process occur primarily at the expression and symbolic stages. Most students bypassed the generalization method, relying instead on formulas or manual calculations. Based on these results, it is recommended that educators implement didactic designs that offer targeted interventions during the expression and symbolic stages, such as using more interactive and symbolic reasoning activities to strengthen students' understanding and generalization skills in number patterns.